2016
DOI: 10.1007/s10750-015-2638-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a comprehension of Ceratium (Dinophyceae) invasion in Brazilian freshwaters: autecology of C. furcoides in subtropical reservoirs

Abstract: Ceratium species are not a common component of freshwater phytoplankton in South America. However, these dinoflagellates have often been observed in many water bodies over the past two and a half decades. We investigated Ceratium furcoides' abundance and morphological variation during its initial phase of colonization (2012)(2013) in two subtropical reservoirs in southern Brazil in order to explore which environmental factors were related to the occurrence, persistence and bloom formation of this dinoflagellat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
43
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 75 publications
12
43
1
13
Order By: Relevance
“…The limnological characterization of these environments, as well as the population dynamics of C. furcoides during the study period, was previously reported by Cavalcante et al. ().…”
Section: Methodssupporting
confidence: 59%
See 2 more Smart Citations
“…The limnological characterization of these environments, as well as the population dynamics of C. furcoides during the study period, was previously reported by Cavalcante et al. ().…”
Section: Methodssupporting
confidence: 59%
“…Ceratium furcoides (Levander) Langhans is a common dinoflagellate in the northern hemisphere, but was not reported in South America until 2003 (Cavalcante et al., ). Since that time, Brazilian phytoplanktologists have been surprised by the introduction and quick expansion of this dinoflagellate in freshwater systems in Brazil (Cavalcante, Cardoso, Sussella, & Becker, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Ceratium seasonal dynamics was well represented by a niche response model based on temperature alone with an optimum of 21 °C (Grover & Chrzanowski, ). Cavalcante et al () reviewed the autoecology of C. furcoides in subtropical reservoirs confirming this growth temperature range.…”
Section: Discussionmentioning
confidence: 85%
“…Such modification in turbulence regimes enables the development of phytoplankton species that cannot develop in fast flowing waters but will progressively achieve large populations on behalf of frequently stratified water columns with sufficient nutrients and light conditions. Reservoirs worldwide are inhabited by phytoplankton assemblages dominated by Microcystis , Dolichospermum , or Ceratium species, forming either mixed or single blooms (Cavalcante, Cardoso, Sussella, & Becker, ; Crosetti & Bicudo, ; Dai, Yang, & Cai, ; Hu & Xiao, ; Jacoby & Kann, ; Matsumura‐Tundisi, Tundisi, Luzia, & Degani, ; Mwara, Koyo, & Zech, ; Oberholster, Botha, & Ashton, ; Te & Gin, ; Znachor et al, ). In South America, the proliferation of cyanobacteria as well as the recent invasion of Ceratium is largely a consequence of building cascades of reservoirs on large rivers (Padisák, Vasas, & Borics, ).…”
Section: Introductionmentioning
confidence: 99%